2013
DOI: 10.1177/1534735413513635
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of Vascular Endothelial Growth Factor via Inactivation of Eukaryotic Elongation Factor 2 by Alkaloids in Coptidis rhizome in Hepatocellular Carcinoma

Abstract: Our study postulates the antiangiogenic effect of CRAE on hepatocellular carcinoma via an eEF2-driven pathway.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(25 citation statements)
references
References 31 publications
0
25
0
Order By: Relevance
“…Rhizoma coptidis , commonly known as Huang Lian in China, has been one of the most important medicinal plants used for the treatment of various diseases in traditional Chinese medicine for more than 2000 years. In recent years, numerous scientific studies have demonstrated that Rhizoma coptidis and its main active constituents display a variety of activities including anti‐bacterial, anti‐cancer, anti‐hyperglycemic, anti‐hyperlipidemic, anti‐diabetic, anti‐obesity, anti‐inflammatory, radio‐protective and hepato‐protective effects . Moreover, Rhizoma coptidis and its isolated alkaloids have been reported to have cardio‐protective and neuro‐protective properties.…”
Section: Introductionmentioning
confidence: 99%
“…Rhizoma coptidis , commonly known as Huang Lian in China, has been one of the most important medicinal plants used for the treatment of various diseases in traditional Chinese medicine for more than 2000 years. In recent years, numerous scientific studies have demonstrated that Rhizoma coptidis and its main active constituents display a variety of activities including anti‐bacterial, anti‐cancer, anti‐hyperglycemic, anti‐hyperlipidemic, anti‐diabetic, anti‐obesity, anti‐inflammatory, radio‐protective and hepato‐protective effects . Moreover, Rhizoma coptidis and its isolated alkaloids have been reported to have cardio‐protective and neuro‐protective properties.…”
Section: Introductionmentioning
confidence: 99%
“…1A), similar to other cancers after treatment of 100 µg/ml CR (17)(18)(19). In addition, we assessed the cell viability in other melanoma cell lines, M14 (BRAF V600E), Malme3M (BRAF V600E), MeWo (no mutation in BRAF and NRAS), and SK-MEL-2 (NRAS Q61R), with a different genetic background (Fig.…”
Section: Cr Inhibits the Cell Viability In Some Melanoma Cell Linesmentioning
confidence: 99%
“…Three batches of HLJDD were analyzed and the common chemical profile of the decoction was generated by recognizing relevant peaks on the chromatogram. Analysis of any heavy metals and organic pesticides contamination were conducted with methods described in our previous study (Tan et al, 2013).…”
Section: Chemical Analysismentioning
confidence: 99%